Impact of Radiofrequency Exposure From Mobile Phones on the Risk of Developing Brain Tumors in Korean and Japanese Adolescents: A MOBI-Kids Case-control Study - Noriko Kojimahara; Yong-Han Lee; Ae-Kyoung Lee; Sanghyuk Bae; Ho-Jang Kwon; Mina Ha; Yasuto Sato; Masao Taki; Joe Wiart; C.E. Langer; Elisabeth Cardis (Journal of Epidemiology, 2024)
Background: This study aimed to examine the association between risk of brain tumors and radiofrequency (RF) exposure from mobile phones among young people in Korea and Japan. Methods: This case-control study of brain tumors in young people was conducted in Korea and Japan under the framework of the international MOBI-Kids study. We included 118 patients diagnosed with brain tumors between 2011 and 2015 and 236 matched appendicitis controls aged 10–24 years. Information on mobile phone use was collected through face-to-face interviews. A detailed RF exposure algorithm, based on the MOBI-Kids algorithm and modified to account for the specificities of Japanese and Korean phones and networks, was used to calculate the odds ratios (ORs) for total cumulative specific energy using conditional logistic regression. Results: The adjusted ORs in the highest tertile of cumulative call time at 1 year before the reference date were 1.61 (95% confidence interval [CI], 0.72–3.60) for all brain tumors and 0.70 (95% CI, 0.16–3.03) for gliomas, with no indication of a trend with exposure. The ORs for glioma specifically, were below 1 in the lowest exposure category. Conclusion: This study provided no evidence of a causal association between mobile phone use and risk of brain tumors as a whole or of glioma specifically. Further research will be required to evaluate the impact of newer technologies of communication in the future.